Funkce růstových faktorů v lidském organismu a jejich využití v medicíně, zejména v ortopedii a traumatologii - Frei, Robert; Biosca, F. E; Handl, Milan; Trč, Tomáš (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2008)
The authors analyze one of the new therapeutic approaches - the use of autologous growth factors. Because the chemical structure of these proteins and their involvement in many functions of the organism affect the whole range of tissues, with a possibility to use them in human medicine. Growth factors, such as platelet-derived growth factor, transforming growth factor and others, exert effects on fibroplastic events during ontogenesis as well as on regeneration of tissues injured due to an accident or surgery. The preparation of therapeutic doses of growth factors consists of autologous blood collection, plasma separation and application of plasma rich in growth factors. The fibroplastic event insolves chemotaxis and proliferation of cells, proteosynthesis, reparation and remodeling of tissues. The paper describes the method and is an introduction to studies on the utilization of growth factors in orthopaedics and traumatology.
Keywords: Regeneration; Intercellular Signaling Peptides and Proteins; lidé; Wound Healing; mezibuněčné signální peptidy a proteiny; Humans; regenerace; hojení ran